The Actions of e-Branding and Content Marketing to Improve Consumer Relationships - Giuseppe Granata; Giancarlo Scozzese (European Scientific Journal, ESJ, 2019)
The way of doing marketing has substantially changed in the digital age. This change represented the direct consequence of a technological revolution that has led to a radical change in the way in which consumers relate to products, companies and markets. Among the most evident manifestations of such process the figure of the cyber consumer emerges, which is characterized by the desire to express the uniqueness through the personalization of products or services one buys, the brands being uses and researched information. Even the prices are often established by the consumer, on the basis of the willingness to pay and the value he attributes to individual goods. The above-mentioned conditions have highlighted the inadequacy of traditional marketing methodologies, focused on the company rather than the consumer and voted for a generally unilateral communication, in responding effectively to these needs. Today, consumers want to maintain transparent relationships with companies through two-way communication, expertly nourished with information and entertainment content and open to external input. The paper's goal is to discuss how internet-related tools can improve marketing content. What are the actions, to be put in place, to improve the marketing and communication in order to achieve a better relationship with the customer. Tools such as digital marketing, e-brand, storytelling, etc., are tools to improve relationships with customers by building a relationship that lasts over time.